2012
DOI: 10.1159/000188068
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation Induces Calcium-dependent Up-regulation of Neuregulin-1� in Dystrophic Skeletal Muscle Cell Lines

Abstract: Duchenne muscular dystrophy (DMD) is a neuromuscular disease originated by reduced or no expression of dystrophin, a cytoskeletal protein that provides structural integrity to muscle fibres. A promising pharmacological treatment for DMD aims to increase the level of a structural dystrophin homolog called utrophin. Neuregulin-1 (NRG-1), a growth factor that potentiates myogenesis, induces utrophin expression in skeletal muscle cells. Microarray analysis of total gene expression allowed us to determine that neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…ES increases Ca 2+ levels and activates nerve growth factor in ES-responsive Schwann cells in vitro [28, 46]. Ca 2+ , a critical second messenger, is involved in many intracellular molecular signaling cascades [47, 48]. Previous studies have shown that Ca 2+ plays important roles in regulating neurite extension triggered by extracellular factors, such an chemicals, neurotrophin or physical stimulation [5, 49, 50].…”
Section: Discussionmentioning
confidence: 99%
“…ES increases Ca 2+ levels and activates nerve growth factor in ES-responsive Schwann cells in vitro [28, 46]. Ca 2+ , a critical second messenger, is involved in many intracellular molecular signaling cascades [47, 48]. Previous studies have shown that Ca 2+ plays important roles in regulating neurite extension triggered by extracellular factors, such an chemicals, neurotrophin or physical stimulation [5, 49, 50].…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts in this line have been focused on promoting contractility of human myotubes, in order to increase maturation and mimic exercise and adaptive responses characteristic of skeletal muscle. Different strategies include exogenous application of electrical pulse stimulation to cultured myotubes [11][12][13][14][15], magnetic fields to induce myoblast differentiation, and co-culturing with spinal cord explants [16][17][18][19] or human motoneurons [20,21] in order to achieve myotube innervation and subsequent maturation. More recently, spontaneous contractile activity has been observed in human myotubes by using a defined differentiation medium containing several trophic factors [22].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have recently described DMD phenotype and genotype, 5 , 6 heart problems, 7 postural adjustment, 8 physical training, 9 multidisciplinary clinical evaluations, 10 , 11 therapeutic treatments, 12 and drug treatment. 13 15 However, there is growing interest in the use of computers by subjects with DMD.…”
Section: Introductionmentioning
confidence: 99%